Tumor necrosis factor-alpha in gestation and puerperium of women with gestational hypertension and pre-eclampsia - Peraçoli, José Carlos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP] (Blackwell Publishing, 2007)
Problem High plasma levels of tumor necrosis factor-alpha (TNF-alpha) in pregnant women have been associated with the pathogenesis of pre-eclampsia (PE). This study evaluated TNF-alpha plasma levels and monocyte production in gestational hypertension (GH) and PE during gestation and at puerperium.Method of study This study included 128 women, of whom 20 were non-pregnant (NP) normotensive (NT), and 108 were pregnant: 36 NT, 27 with GH, and 45 with PE. Peripheral blood plasma was used for TNF-alpha and uric acid determination. TNF-alpha was determined in plasma and lipopolysaccharide (LPS)-stimulated and non-stimulated monocyte supernatants by L929 bioassay.Results Tumor necrosis factor-alpha and uric acid plasma levels were higher in PE than in GH pregnancies. In both hypertensive groups, these parameters positively correlated and were significantly more elevated than in NT and NP women. TNF-alpha plasma levels and monocyte production were higher in hypertensive than in NT women during gestation, and significantly decreased at puerperium. Although decreased, TNF-alpha release in LPS-stimulated PE monocytes, was still significantly higher than in the other pregnant groups.Conclusion In vivo monocyte activation in GH and PE pregnant women was characterized by in vitro TNF-alpha production. The fact that higher circulating concentrations of TNF-alpha and uric acid were observed in PE than in GH suggests an association with disease severity.
Keywords: monocytes; pre-eclampsia; pregnancy; puerperium; tumor necrosis factor-alpha